Innovation Ways of Management of Library - Khudaybergenova Marjan Baltabaevna (International Journal on Integrated Education, 2021)
This article discusses new management methods using modern methods and technologies in the management of library activities and information resource center. This article also provides information on the world’s most advanced library management systems, methods, and Fayol’s systems.